Introductory Accounting–A Managerial Emphasis (Book). - Peterson, Ron; Spiller, Earl A. (The Accounting Review, 1974)
Abstract Reviews the book 'Introductory Accounting–A Managerial Emphasis,' by E. Bryan Smyth and Walter L. Burke.